2018
DOI: 10.3390/ijerph15122909
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Nutrition and Physical Activity in Childcare: Views from Childcare Managers, Childcare Workers and Parents on Influential Factors

Abstract: Childhood obesity is an important public health issue influenced by both personal and environmental factors. The childcare setting plays an important role in children’s energy balance-related behaviours (EBRB), such as physical activity, sedentary behaviour and healthy nutrition. This study aimed to explore facilitators and barriers of healthy EBRB in childcare in a comprehensive way, from the perspective of three crucial stakeholders: childcare managers, childcare workers and parents. A qualitative study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 72 publications
(94 reference statements)
0
29
0
Order By: Relevance
“…Studies have shown the importance of determinants in different types of environments on physical activity and sedentary behavior [36,61,62]. Systematic reviews have also stressed the importance of integrated interventions, i.e., combining the physical and sociocultural environment [63,64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown the importance of determinants in different types of environments on physical activity and sedentary behavior [36,61,62]. Systematic reviews have also stressed the importance of integrated interventions, i.e., combining the physical and sociocultural environment [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…SuperFIT was developed in partnership with the intervention preschool organization, a local PA providing organization, and health promotion experts. Formative research [36], practice-based knowledge of cooperating partners, and theory-and evidence-based knowledge [26,[37][38][39][40] were used to develop it. Further, a continuous process of co-creation, feedback and adaptations was adopted during development to increase suitability and applicability in the settings.…”
Section: The Interventionmentioning
confidence: 99%
“…In a recent qualitative study in the US, ECE providers reported that the ECE environment had the potential to exert a strong influence over children and was an ideal setting for introducing less familiar foods [46]. In another qualitative study in the Netherlands, managers believed it was vital to encourage healthy eating for the children in their care [47]. Managers emphasized the importance of making healthy foods, like fruits and vegetables, readily available in the ECE environment [47].…”
Section: Discussionmentioning
confidence: 99%
“…In another qualitative study in the Netherlands, managers believed it was vital to encourage healthy eating for the children in their care [47]. Managers emphasized the importance of making healthy foods, like fruits and vegetables, readily available in the ECE environment [47].…”
Section: Discussionmentioning
confidence: 99%
“…A steering committee of stakeholders, including the municipality, community health service and youth health care agency, were consulted during the process of development and implementation. As formative research for the intervention development, a needs assessment was performed among preschool teachers and parents of the target population [48]. The theory and evidence-based knowledge from the health promotion experts, practice-based knowledge of the partners, and the input of the formative research were used to develop the different intervention components and strategies.…”
Section: The Interventionmentioning
confidence: 99%